Recovery kinetics of short-term depression of GABAergic and glutamatergic synapses at layer 2/3 pyramidal cells in the mouse barrel cortex - Lombardi, Aniello; Wang, Qiang; Stüttgen, Maik C.; Mittmann, Thomas; Luhmann, Heiko J.; Kilb, Werner (Frontiers in Cellular Neuroscience, 2023)
Short-term synaptic plasticity (STP) is a widespread mechanism underlying activity-dependent modifications of cortical networks. To investigate how STP influences excitatory and inhibitory synapses in layer 2/3 of mouse barrel cortex, we combined whole-cell patch-clamp recordings from visually identified pyramidal neurons (PyrN) and parvalbumin-positive interneurons (PV-IN) of cortical layer 2/3 in acute slices with electrical stimulation of afferent fibers in layer 4 and optogenetic activation of PV-IN. These experiments revealed that electrical burst stimulation (10 pulses at 10 Hz) of layer 4 afferents to layer 2/3 neurons induced comparable short-term depression (STD) of glutamatergic postsynaptic currents (PSCs) in PyrN and in PV-IN, while disynaptic GABAergic PSCs in PyrN showed a stronger depression. Burst-induced depression of glutamatergic PSCs decayed within <4 s, while the decay of GABAergic PSCs required >11 s. Optogeneticallyinduced GABAergic PSCs in PyrN also demonstrated STD after burst stimulation, with a decay of >11s. Excitatory postsynaptic potentials (EPSPs) in PyrN were unaffected after electrical burst stimulation, while a selective optogenetic STD of GABAergic synapses caused a transient increase of electrically evoked EPSPs in PyrN. In summary, these results demonstrate substantial short-term plasticity at all synapses investigated and suggest that the prominent STD observed in GABAergic synapses can moderate the functional efficacy of glutamatergic STD after repetitive synaptic 2 This is a provisional file, not the final typeset article stimulations. This mechanism may contribute to a reliable information flow towards the integrative layer 2/3 for complex time-varying sensory stimuli.